Principles of Human Subjects Protections Applied in an Opt-Out, De-identified Biobank - Pulley, Jill; Clayton, Ellen; Bernard, Gordon R.; Roden, Dan M.; Masys, Daniel R. (Clinical and translational science, 2010)
BioVU, the Vanderbilt DNA Databank, is one of few biobanks that qualifies as non‐human subjects research as determined by the local IRB and the federal Office of Human Research Protections (OHRP). BioVU accrues DNA samples extracted from leftover blood remaining from routine clinical testing. The resource is linked to a de‐identified version of data extracted from an Electronic Medical Record (EMR) system, termed the Synthetic Device (SD), in which all personal identifiers have been removed. Thus, there is no identifiable private information attached to the records. The Belmont Report enumerates the importance of the boundary between practice and research, and three principles: Respect for Persons, Beneficence, and Justice, which constitute the essential ethical framework by which IRBs and ethics committees judge the risks and benefi ts of research involving human subjects. BioVU was developed by designing and implementing new procedures, for which there were no previously established methods, which are consistent with the principles of the Belmont Report. These included special oversight and governance, new informatics technologies, provisions to accommodate patients’ preferences, as well as an extensive public education and communications component. Considerations of core principles and protections in the practical implementation of BioVU is the focus of this paper. Clin Trans Sci 2010; Volume #: 1–7